The children's programme: a description of a group and family intervention for children engaging in problematic and harmful sexual behaviour and their parents/carers. Issue 2 (4th May 2019) - Barry, Stephen; Harris, Emma
ABSTRACT: Children under 10 are increasingly being referred to services for concerning problematic or harmful sexual behaviour, but information about interventions to support these children and their families is limited. A 3-year pilot of a group cognitive–behavioural intervention for children and their parents/carers is described. Forty-nine children were referred to the programme with 27 completing the programme in this period. This is the first intervention of its kind to be delivered with a UK population and demographic information is provided about the children who have been assessed, including information about age, gender, family composition and abuse history. Outcome data from the Trauma Symptom Checklist for Children, Child Sexual Behaviour Inventory, Strengths and Difficulties Questionnaire and the Parental Stress and Social Support Scale is reported. The available outcome data indicates the group has been largely beneficial in reducing problematic sexual behaviour. Key learning and implications for practice are discussed.